Effect of Adding 1,4-Butanediol and Polyethylene Glycol (PEG) 1000 to the Ease of Bioplastic Biodegradation from Jackfruit Beans (Artocarpus heterophyllus) - Argo Khoirul Anas; Nanang Rudianto Ariefta; Yuni Nurfiana; Eli Rohaeti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
The influences of plasticizer on the biodegradability of bioplastic film synthesized from starch obtained from jackfruit seeds with a help of Acetobacter xylinum were investigated. In this study, 1,4-butanediol and polyethylene glycol (PEG) 1000 were used as plasticizer. The biodegradation behavior of the resulted bioplastic films was characterized by calculating changes in their mass loss and rate of mass loss. The Fourier Transform Infrared (FTIR) spectroscopy was also conducted to analyze theirfunctional group. The results shows that all the bioplastic films were well biodegradated, where PEG 1000 with concentration of 0,5% and 1,0% can successfully improve the biodegradability of bioplastic film. Meanwhile, the used of 1,4-butanediol with concentration of 0,5% and 1,0% can increase and decrease the biodegradability of sample, respectively.